(untitled) (Ar Rehla: Journal of Islamic Tourism Halal Food Islamic Traveling and Creative Economy, 2025)
Abstract: The commercialization of halal certification in Indonesia has shifted its function from a religious safeguard to an economic commodity. This development raises concerns about the balance between spiritual values and market-driven practices. This study aims to critically analyze three major aspects of this phenomenon: the use of halal labels as branding tools, the rise of external halal consultants, and the financial implications of certification fees, particularly for micro, small, and medium-sized enterprises (MSMEs). Using a descriptive qualitative approach, data were collected through document analysis of government regulations, scholarly articles, online news, and BPJPH publications. The findings show that certification fees, fast-track services, and consultant involvement reinforce the commercial orientation of halal certification. While these mechanisms increase administrative efficiency, they also impose financial burdens on MSMEs and reduce the spiritual integrity previously associated with halal assurance. The results further reveal that non-Muslim companies actively adopt halal labels to compete in the Muslim consumer market, strengthening the commodification of religious symbols. The study concludes that without stronger regulatory oversight and ethical standards, commercialization may erode public trust and weaken the religious significance of halal certification. These findings highlight the urgency of policy reforms to maintain authenticity, fairness, and accountability within Indonesia’s halal certification system. Keywords: Indonesian food industry; halal certification; commercialization Abstract: Komersialisasi sertifikasi halal di Indonesia telah menggeser fungsinya dari penjaga kepatuhan religius menjadi komoditas ekonomi. Perkembangan ini menimbulkan kekhawatiran mengenai keseimbangan antara nilai spiritual dan praktik pasar yang berorientasi profit. Penelitian ini bertujuan menganalisis secara kritis tiga aspek utama fenomena tersebut: penggunaan label halal sebagai strategi branding, munculnya konsultan halal eksternal, serta implikasi finansial dari tarif sertifikasi terutama bagi pelaku usaha mikro, kecil, dan menengah (UMKM). Penelitian menggunakan metode deskriptif kualitatif melalui analisis dokumen terhadap regulasi pemerintah, artikel ilmiah, berita daring, dan publikasi BPJPH. Hasil penelitian menunjukkan bahwa tarif sertifikasi, layanan fast-track, serta keterlibatan konsultan memperkuat orientasi komersial dalam proses sertifikasi halal. Mekanisme ini memang meningkatkan efisiensi administratif, tetapi juga menambah beban biaya bagi UMKM dan mengurangi integritas spiritual yang sebelumnya melekat pada jaminan halal. Temuan lain menunjukkan bahwa perusahaan non-Muslim turut memanfaatkan label halal untuk bersaing di pasar konsumen Muslim, sehingga memperkuat komodifikasi simbol keagamaan. Penelitian menyimpulkan bahwa tanpa pengawasan regulatif dan standar etika yang lebih kuat, komersialisasi berpotensi mengikis kepercayaan publik dan melemahkan makna religius sertifikasi halal. Temuan ini menegaskan urgensi reformasi kebijakan untuk menjaga autentisitas, keadilan, dan akuntabilitas sistem sertifikasi halal di Indonesia. Keywords: industri makanan Indonesia; sertifikasi halal; komersialisasi